Poggyászunk Kádár János - Sólyom, András (Hungary : MTV, 2006)
The documentary looks at the legacy of the Kádár era in Hungary. János Kádár (1912 –1989) was a Hungarian communist leader and the General Secretary of the Hungarian Socialist Workers' Party, presiding over the country from 1956 until 1988.
Keywords: Documentary films